PENGARUH TERPAAN INFORMASI DERETAN KASUS POLRI DAN CITRA POLRI SEBAGAI INSTITUSI NEGARA TERHADAP KEPERCAYAAN PUBLIK PADA KEPOLISIAN REPUBLIK INDONESIA - Athallah Akmal Dhiaulhaq; Yohanes Thianika Budiarsa (Interaksi Online, 2026)
Public trust in state institutions is a crucial indicator in assessing the effectiveness of their performance. In this context the Indonesian National Police (POLRI) is one of the mostscrutinized institutions by the public due to its central role in society. In recent years, POLRIhas been exposed to extensive media coverage regarding a series of cases involving theinstitution. As a result, many members of the public have expressed criticism and evaluationsthrough social media platforms. This study aims to examine the effects of information exposureon public trust in POLRI, as well as the effect of POLRI’s image on public trust in theIndonesian National Police. This study employs a quantitative approach using method throughquestionnaire distributed to 152 respondents residing in the JABODETABEK area, agedbetween 18 and 45 years, who actively using use social media and have previously receivedservices from POLRI. The data were analyzed using simple linear regression. The resultsindicate that both information exposure and POLRI’s image have a significant effect on publictrust, with significance values of ,018 and ,000 respectively. The findings also reveal that themajority of respondents have a low level of information exposure (51,33%) and perceivePOLRI’s image negatively (73,33%). Despite the relatively low level of information exposure,the results show that the low level of public trust in POLRI (54,66%) is significantly influencedby both information exposure and POLRI’s image.